Biological Analogies Between Some fig-wasps (Hymenoptera: Agaonidae and Toryrnidae: Sycophaginae) and Varroa jacobsoni (Acari: Varroidae) - Ramírez B., William (1987)
Some fig wasps (Agaonidae and Torymidae: Sycophaginae) and the mite Varroa jacobsoni exhibit analogous biological, morphological and behavioral characteristics that seem to have arisen through convergent evolution. Both groups develop in enclosed dark environments (small territories) with both high internal humidity and carbon dioxide concentration. The males of both groups are haploid, exhibit neoteny, and have shorter developmental phases and life spans than females. They do not fight at mating nor feed as adults. They are also less numerous and less sclerotized than the females. Male and female Varroa have enlarged peritremata and breathing tubes. Laminate breathing peritremal excrescenses or filaments are found in the Sycophaginae males (except Idarnes). The presence of large peritremata and protrudingbreathing structures, among other analogies between some fig wasps and the acarids, Varroa, seem to be adpatations to the humid environments in which they Jive during part of their life cycle.Organisms that develop in closed microenvironments (seraglia) with very similar and constant physical, biological and feeding conditions, seem to have very constant ontogenesis and also develop specific one-to-one relationships; that is, each host has a specific associate (parasite or symbiont) . This type of association leads to radiative adaptations, synchronism of development for at least one of the associates and total dependence for at least one of the partners. They also show a high degree of relatedness.Both Agaonidae and Varroa fit the "Local Mate Competition Rule" of Hamilton. Other characteristics that seem to fit into Hamilton's rule are: specific relationships between host and associate, developmental synchronization, associate females usually lay a constant number of eggs; nearly constant developmental time from egg to adult of the associate, neotenic males, very constant ontogenies of one of the associates and precise sex ratios.